К проблеме литовско-белорусских лексических связей - Чекман, Валерий Николаевич (Baltistica, 1972)
ON THE PROBLEM OF LITHUANIAN-BYELORUSSIAN LEXICAL CONTACTS This paper deals with some translation loans in Byelorussian from Lithuanian, namely, ten semantic loans (the type of blr. адбіты “enclosed, fenced” <lith. atmùšti “to enclose, to fence”; blr. адбіцца “coire” < lith. atsimùšti “to mate”; blr. каза́ “blemish, flaw” <lith. ožỹs, ožkà; blr. сярэ́дзіна “waist” < lith. pusiáujas etc.), eigt word-building loans (the type of blr. абія́кі < lith. apmuštìniai (klumpės) “kind of wooden boots”; blr. акі́дацца < lith. apsimèsti “to slip on”; blr. вы́стрыгаць < lith. iškir̃pti “to cut out”; blr. приты́ка < lith. priẽkaištas “reproach” etc.) and three cases of loans of morphological formant (blr. бураке́ “borshch” < lith. burókai; blr. вайлакі́ < “kind of felt boots, valenki” < lith. veĩlokai; blr. кру́пы “groats” < lith. kruõpos). The author believes the translation loans can be considered as an essential linguistic argument in favour of the hypothesis about the great role of the Baltic substratum in forming Byelorussian dialects.